In‐situ Observation of γ' Phase Transformation Dynamics during Selective Laser Melting of CMSX‐4 - Wahlmann, Benjamin; Krohmer, Erwin; Breuning, Christoph; Schell, Norbert; Staron, Peter; Uhlmann, Eckart; Körner, Carolin (Advanced Engineering Materials, 2021)
Additive manufacturing (AM) of superalloys has been attracting increasing interest. While most studies focus on the processability and mechanical properties of the finished product, it is also necessary to understand the phase transformations during the consecutive melting processes. In this study, the precipitation and dissolution of the γ′ phase in the Ni‐base superalloy CMSX–4 in a selective laser melting process is reported. These phase transformations are studied in‐situ by small‐angle X‐ray scattering (SAXS) during AM. Concurrent wide‐angle X‐ray scattering (WAXS) provides information on the evolution of lattice parameters and temperature during the process. Additional thermal and thermodynamic simulations were peformed to support the experiments. The investigations were focused on the influence of different beam scanning strategies as well as the effect of laser power and scanning speed on the phase transformation dynamics. Due to the high cooling and heating rates inherent to AM, phase transformations occurred far off‐equilibrium. Both precipitation and dissolution of γ′ phase were observed. The scan strategies are shown to have a considerable effect on the phase transformation dynamics, which exceeded the impact of the beam parameters. The study demonstrates the capability of combined SAXS and WAXS for the in‐situ study of phase transformations in AM processe
Keywords: additive manufacturing; phase transformations; x-ray scattering; in-situ measurements